2000
DOI: 10.1053/joca.2000.0361
|View full text |Cite
|
Sign up to set email alerts
|

A report of the Osteoarthritis Research Society International Standing Committee for Clinical Trials Response Criteria Initiative

Abstract: Based on data from clinical trials, two sets of responder criteria have been developed that can categorize an individual's responses to treatment in a clinical trial. These responder criteria require validation in additional datasets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
1
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(139 citation statements)
references
References 11 publications
6
127
1
3
Order By: Relevance
“…These include a high placebo effect, the design of the study, and the lack of efficacy of the drug itself (25). IA procedure, notably with injections of HA into the knee, is commonly associated with a high placebo response that might limit the ability to detect benefits of the treatment (8,22,25). However, in the present study we did not observe a high placebo response that may have skewed the results observed in the treatment group.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…These include a high placebo effect, the design of the study, and the lack of efficacy of the drug itself (25). IA procedure, notably with injections of HA into the knee, is commonly associated with a high placebo response that might limit the ability to detect benefits of the treatment (8,22,25). However, in the present study we did not observe a high placebo response that may have skewed the results observed in the treatment group.…”
Section: Discussioncontrasting
confidence: 55%
“…The severity of pain was evaluated at each visit by use of a continuous 100-mm VAS assessing the global level of pain in the target hip, regardless of the circumstances over the previous 48 hours. Secondary outcomes were the proportion of responders, defined according to the OARSI criteria (22); the Western Ontario and McMaster Universities Osteoarthritis Index global score and subscores for pain, stiffness, and disability (23); the patient and physician global assessment of the severity of hip OA measured on a 100-mm VAS; and treatment with analgesics and NSAIDs. Outcomes were measured at inclusion and at baseline (immediately before injection).…”
Section: Methodsmentioning
confidence: 99%
“…Further, a change of 20 mm has been defined as the minimum required for classification as a primary responder by Osteoarthritis Research Society International (29,30). Accordingly, we deemed that an improvement in the PES-treated group of 20 mm greater than that achieved in the placebo group would constitute a clinically meaningful and important difference.…”
Section: Methodsmentioning
confidence: 99%
“…visual analogue scale [VAS] 31,32 These criteria have been validated and were used in four of the larger lumiracoxib studies reported in this review to analyse response to treatment. This review examines all clinical efficacy studies conducted to date that compared lumiracoxib with placebo, traditional NSAIDs or other COX-2 selective inhibitors in patients with OA.…”
Section: Efficacy Of Lumiracoxib In Osteoarthritismentioning
confidence: 99%